(untitled) (Palíndromo, 2020)
From the beginning of the 19th century up to the present, ornament has faced different crises because it is not an autonomous art but traditionally attached to a surface, be it architecture or applied arts. The fate of ornament has varied, according to leading theorists and critics in these fields. In 1812, Percier and Fontaine exhorted architects and artisans to use ornament with consciousness and care. Gottfried Semper could even conceive of applied arts without ornament, and his utmost concern was to show the original function of objects that they had lost over time. He wanted to clarify the purpose of an object, not only from a functional point of view, but also iconographically. Christopher Dresser, with a background as a biologist and ‘ornamentist’, was the first industrial designer to create objects without ornament, following the influence of Japanese art. The death knell apparently tolled for ornament in 1908 with Adolf Loos’ talk on Ornament and Crime. The subsequent opposition of Art Deco and Modernism was a clash of cultures, perceptible even nowadays among architects and art historians. At a certain point, as recent studies have pointed out, there was a merging of these two art movements. At present, ornament has made a comeback and been reintegrated into architecture in a new way and spirit.